Penyusunan Dokumen Masterplan Pengembangan Ekowisata Desa Datar Ajab Kabupaten Hulu Sungai Tengah - Abdan, Indra Suci; Hamid, Ismar; Nadiba, Shaffa; Hamdi, Resyda Syaibatul; Lisdawanti; Azzahra, Shamiyah Noor; Ramadhan, Ahmad; Ramadhan, Akhmad David; Thiansyah, Adhera Nur; Yahya, Nur Azima; Putri, Maziatul; Rahmawati; Hariadi (Prodi Sosiologi FISIP ULM, 2025)
Karang Taruna plays a crucial role in enhancing the social life of the community, particularly in Hinas Kanan Village, Hantakan District. The region has seen a decline in youth engagement in improving the quality of the younger generation, especially in terms of creativity and critical thinking skills. This served as the motivation for the service team to reactivate the Karang Taruna organization to develop and enrich the youth's understanding of their contributions to sustainable development. The younger generation has the potential to maximize the role of Karang Taruna in empowering the community's social welfare. The program aims to create a beneficial atmosphere through various social activities such as organizing Focus Group Discussions on village potential, commemorating the Republic of Indonesia's anniversary with the youth, conducting joint clean-up actions, and exploring tourist attractions with the village youth. The staff team has conducted workshops to strengthen the vision of Karang Taruna with the members and village officials, fostering solidarity and social responsibility among the youth of Hinas Kanan village. This aims to encourage a more active role in community development and greater sensitivity to social issues in their environment. The research emphasizes the importance of the active role of youth in sustainable development and their involvement in decision-making for the future of the village. It can serve as a reference for youth empowerment programs in other villages facing similar challenges and aid in designing more effective and sustainable strategies.